Technetium Tc 99m sulphur colloid seminal vesicle scintigraphy: A novel approach for the diagnosis of the ejaculatory duct obstruction - Orhan, Irfan; Duksal, Imed; Onur, Rahmi; Balcl, Tansel Ansal; Poyraz, Kuersad; Firdolas, Fatih; Kadioglu, Ates (Elsevier Science Inc, 2008)
OBJECTIVES To define a novel technique in the diagnosis of partial and complete ejaculatory duct obstruction (EDO). METHODS Twenty men with suspected EDO were initially evaluated by transrectal ultrasound (TRUS). Subsequently, all patients underwent TRUS-guided seminal vesicle (SV) scintigraphy. Technetium Tc 99m sulphur colloid solution was injected into each SV under TRUS guidance and patients were immediately evaluated by scintigraphy. After patients ejaculated scintigraphy was repeated. The difference between 2 measurements in respect to technetium Tc 99m count was used to measure the percentage of emptying. RESULTS In the first group, TRUS revealed 11 patients with findings suggestive of EDO, whereas no abnormality was found in 9. Scintigraphic measurement in first group of patients showed a mean emptying ratio for the right and left SVs of 16.6% +/- 2.22 (2.2 to 30.6) and 17.1% +/- 2.34 (1-4 to 32.5), respectively. The mean percent of emptied technetium Tc 99m from right and left SVs in patients with no pathologic findings on TRUS was 30.9% +/- 4.3 (10.1 to 44.2) and 33.9% +/- 5.81 (13.6 to 68.1), respectively. Statistically significant difference was determined between 2 groups (P = 0.037). initially, TRUS examination revealed no pathologic findings in 3 patients; however, SV scintigraphy showed less than 30% emptying and revealed an additional 33% of patients to be obstructed in our series. CONCLUSIONS TRUS, the static anatomic imaging modality, may not be sufficient to distinguish functional from complete obstruction. Seminal vesicle scintigraphy is unique that incorporates physiologic aspect of ejaculation into a diagnostic intervention, of which we believe that is especially important in diagnosis of functional EDO.
Keywords: Aspiration